The Effect Using Animated Video as Teaching Media: (A Case Study at Grade Seventh Academic Year 2023/2024 Of MTSN 6 Tulungangung) - Valentina ‘Ainur Rofiqoh; Dina Kartikawati (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Teaching writing is not easy. Teacher needs to think the appropriate and effective medium that will be able to attract the students’ interest. Due to this case, an animated video was chosen as a medium to facilitate students' learning process to be more interactive and attract students' interest for composing, particularly to write Descriptive Texts. The research explored the use animated videos to teach descriptive text in grade seventh academic year 2023/2024 at MTsN 6 Tulungagung. The type of experiment utilized is a Quantitative with Pre-Experiment Designs. The sample consisted of 31 students as control group. There are three steps conducting this research: pre-test, treatment, and post-test. The expert formed the validation of the questions. Based of the data analysis results, the pre-experimental class’s mean scores 76.35 and 86.32 in the post-test. Researchers found that the score of Sig. (2-Tailed) is 0.001 less than 0.05, therefore H0 is denied by acceptance of Ha. So in this case it was concluded that the differences in the analysis of the mean between the results of the pre and post-test meant that there were effects of using the animated video as the medium of learning in writing Descriptive Text in class VII in the 2023/2024 school year at MTsN 6 Tulungagung.